Impact of Blood Vessel Quantity and Vascular Expression of CD133 and ICAM-1 on Survival of Glioblastoma Patients. (8th November 2017) - Minajeva, Ave; Kase, Marju; Saretok, Mikk; Adamson-Raieste, Aidi; Kase, Sandra; Niinepuu, Kristi; Vardja, Markus; Asser, Toomas; Jaal, Jana
Abstract : Glioblastoma (GB) is the most angiogenic tumor. Nevertheless, antiangiogenic therapy has not shown significant clinical efficacy. The aim of this study was to assess blood vessel characteristics on survival of GB patients. Surgically excised GB tissues were histologically examined for overall proportion of glomeruloid microvascular proliferation (MP) and the total number of blood vessels. Also, immunohistochemical vascular staining intensities of CD133 and ICAM-1 were determined. Vessel parameters were correlated with patients' overall survival. The survival time depended on the number of blood vessels (p = 0.03 ) but not on the proportion of MP. Median survival times for patients with low (<median) and high (≥median) number of blood vessels were 9.0 months (95% CI: 7.5–10.5) and 12.0 months (95% CI: 9.3–14.7). Also, median survival times for patients with low (<median) and high (≥median) vascular expression level of CD133 were 9.0 months (95% CI: 8.0–10.1) and 12.0 months (95% CI: 10.3–13.7). In contrast, the staining intensity of vascular ICAM-1 did not affect survival. In multivariate analysis, the number of blood vessels emerged as an independent predictor for longer overall survival (HR: 2.4, 95% CI: 1.2–5.0, p = 0.02 ). For success in antiangiogenic therapy, better understanding about tumor vasculature biology is needed.